Formação e Expansão do Plano Urbano do Núcleo Central de Guarapari: uma abordagem morfológica entre os séculos XVI e XXI - Monjardim, Manoela Paulinelli Cunha Maiolli (2023)
This paper was developed in the Architecture and Urbanism Post-Graduation Programme of Universidade Federal do Espírito Santo, and encompasses the theoretical field of the study on urban free-use spaces for public use and the urban form, in understanding the first aforementioned is inherent to the second. Starting from the comprehension as seen in Conzen that historical centers are, in general, the oldest parts of cities and the ones which are most subject to modifications, this paper aims to study the core of the city of Guarapari’s central urban area as the empirical object. This way, the objective in this study was to analyze the morphological transformations which happened in the central town plan of the city of Guarapari, in Espírito Santo, from the XVI century until recent days. As for the methodological strategy, an exploratory and explanatory research has been developed which relied on the conceptual bases of the English School of Urban Morphology, through a historical-geographic approach. Mappings, photographs, travelers’ reports, theses, essays and books were the pillars for the development of the research, whilst redesigning was the essential tool to translate the acquired knowledge into cartographic basis. The results were presented through five established morphologic periods: morphogenesis (1557-1863), the occupation of downtown (1863-1902), the expansion to the south (1902-1952), the enclosure with the beaches (1952-1968), and urban coastal landscape (1968-2022). In order to direct the logical thought process, this essay was structured in four chapters: the theoretical, conceptual and methodological bases, which deal with town plan and urban morphology; the application of the case study, which expatiates on the city of Guarapari and deepens the area of study; the morphological analysis, which presents five time periods as well as their historic and evolutive process; and final considerations.